EFFECT OF INTEGRATED USE OF FYM AND UREA ON YIELD, NUTRIENT UPTAKE AND PROTEIN CONTENT OF WHEAT (TRITICUM AESTIVAM L.) - NAVRANG, SANDEEP; TOMAR, G. S. (The Bioscan, 2016)
The present investigation was conducted for one rabi seasons during 2013-14 in a clay loam soil at the Instructional Farm, Indira Gandhi Krishi Vishwavidyalaya, Raipur, (C.G.), India. To study the effect of integrated use of FYM and urea on yield, nutrient uptake and protein content of wheat (Triticum aestivum L.) The result revealed that the highest values of grain yield (4744.11 kg ha-1) were obtained from M1 N2 (SWI at 75% N from urea and 25% N from FYM) which differed significantly over rest of the treatment combinations. However, the maximum nutrient (N,P and K) uptake by wheat in method of sowing and integrated use of FYM and urea respectively in SWI the maximum nutrient uptake by wheat 63.20,15.79,122.63 in integrated use of FYM and urea 74.77, 24.95,142.37 kg ha-1 were observed in the treatment receiving at 75% N from urea and 25% N from FYM and also highest protein content in SWI 9.44% and integrated use of FYM and urea 11.05% (100 % N through urea). Thus, integrated use of FYM and urea improve the crop yields, produces quality grain as well as improve the soil fertility